Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone

Cost Effectiveness of Interactive Radio Instruction Program Karnataka: Basic and Program Cost Effectiveness - Bakshi, Shubhashansha (Working Papers, 2011)
The Program CEA extends to the study to an impact analysis of the Radio programs to assess whether the expenditure being made for this intervention is helping the students in improving their learning outcomes. This would then serve as a true measure of effectiveness that is; linking the outreach with the outcomes. This requires tracking a cohort of treatment and control groups over a period of three years. Also the study has documented the qualitative behaviour as observed in these groups. URL:[http://cbps.in/Publications.aspx].
Keywords: Attendance; CEA; Central Tendency; Cost Effectiveness; Enrolment; Interactive Radio Instruction Program; Karnataka; Qualitative analysis; Research; Teachers; cohort of treatment; data; outcomes; qualitative behaviour; school; villages

Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers - Hanemann, Ulrike; Scarpino, Cassandra (UNESCO Institute for Lifelong Learning, 2016)
The UNESCO Institute for Lifelong Learning (UIL) has published a second edition of "Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers." This compilation of case studies from all world regions presents promising literacy and numeracy programmes that use information and communication technologies (ICTs) in their access and outreach strategies. The twenty-six case studies illustrate how ICTs such as radio, TV, mobile phones, tablets and computers can be used as media of instruction, can supplement face-to-face teaching, and can help to develop and strengthen youth and adult literacy, language and numeracy skills. The case studies featured in this publication can also be found in the UNESCO Effective Literacy and Numeracy Practices Database (LitBase). [For the 1st Edition: "Harnessing the Potential of ICTs for Literacy Teaching and Learning: Effective Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets, and Computers," see ED560504.]
Keywords: Adult Literacy; Case Studies; Distance Education; Educational Technology; Foreign Countries; Handheld Devices; Instructional Materials; Literacy Education; Mathematics Education; Numeracy; Program Content; Program Effectiveness; Radio; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; Television; Videoconferencing

Interactive Radio Instruction : A Successful Permanent Pilot Project? - Trucano, Michael (World Bank Blogs, 2010)
Despite their increased diffusion through rich and poor communities around the world, many people still have serious reservations about large scale investments in information and communication technologies (ICTs) within education systems. Spirited and long-running related debates related to their costs ("too expensive", their critics say), appropriateness ("students needs lots of ...
Keywords: ___working_potential_duplicate

Interactive Radio Instruction : A Successful Permanent Pilot Project? - Trucano, M. (2010)
Despite their increased diffusion through rich and poor communities around the world, many people still have serious reservations about large scale investments in information and communication technologies (ICTs) within education systems. Spirited and long-running related debates related to their costs ("too expensive", their critics say), appropriateness ("students needs lots of ...
Keywords: Commitment; Cost; Equity & access; ___working_potential_duplicate

Interactive Radio Instruction : A Successful Permanent Pilot Project? - Trucano, Michael (World Bank Blogs, 2010)
Despite their increased diffusion through rich and poor communities around the world, many people still have serious reservations about large scale investments in information and communication technologies (ICTs) within education systems. Spirited and long-running related debates related to their costs ("too expensive", their critics say), appropriateness ("students needs lots of ...
Keywords: ___working_potential_duplicate

Interactive Radio Instruction : a successful permanent pilot project? - Trucano, Michael (2010)
Despite their increased diffusion through rich and poor communities around the world, many people still have serious reservations about large scale investments in information and communication technologies (ICTs) within education systems. Spirited and long-running related debates related to their costs ("too expensive", their critics say), appropriateness ("students needs lots of ...
Keywords: ___working_potential_duplicate

UNESCO | Statistics on Radio - UNESCO (2013)

Teaching Writing with Radio - Levine, Sarah; Franzel, Johanna (English Journal, 2015)
Keywords: ⛔ No DOI found

ECT 300 Educational Technology: What are some of the limitations of using live radio broadcasts in teaching? - Nasib, Tim (somi, 2017)
CHAPTER 6  EDUCATIONAL BROADCASTING 6a v).Analyze some of the limitations of using live radio broadcasts in teaching. 6.7 Limitations of live radio broadcasts. As mentioned earlier in this unit eve…

Learning English Language by Radio in Primary Schools in Kenya - Odera, Florence (2011)
Learning English Language by Radio in Primary Schools in Kenya By Florence Y. Odera (PhD) P.O.Box 2303, Kisumu, Kenya Introduction and background information One of the
Keywords: ___working_potential_duplicate

Edutainment Radio, Women’s Status and Primary School Participation: Evidence from Cambodia - Cheung, Maria (2012)
This paper explores the eﬀect of being exposed to education-entertainment (“edutaiment”) gender-related radio information on women’s status and primary school participation. Speciﬁcally, I examine one of the most popular radio stations in Cambodia using two identiﬁcation strategies. The ﬁrst exploits plausible exogenous variation in over-the-air signal strength between radio transmitters and villages within a district. The second exploits the variation across time and space in exposure. Using individual data, both approaches show that access to both entertaining and educating information about gender issues had a signiﬁcant impact on behavior by raising the women’s decision-making power within the household and increasing children’s primary school attendance. The impact was found in both poor and rural households conﬁrming that en radio broadcast is an eﬀective way to transmit information in the more marginalized areas. Suggestive evidence shows that the exposure also aﬀected attitudes towards domestic violence and the prevalence of son preference which is a stepping stone towards changing socially constructed gender norms. The eﬀect on investing in children’s human capital is also reﬂected by higher primary school enrollment three years after exposure.
Keywords: ⛔ No DOI found

Radio Instruction to Strengthen Education and Zanzibar Teacher Upgrading by Radio: Post Project Evaluation - Education Development Center (2015)

Tiyende! Let’s Walk! - Save the Children (2017)
Singilton Phiri Interactive Radio Instruction Specialist Save the Children in Malawi June 16, 2017 Before the introduction of sponsorship in rural Zomba in Malawi, walking...Read the full article...

Students Awareness and Utilization of Educational Broadcasts to Learn in Ogbomoso, Oyo State Nigeria - Olumorin, Charles Olubode; Aderoju, Musiliu Adekola; Onojah, Amos Ochayi (Turkish Online Journal of Distance Education, 2018)
Radio and Television are broadcast media meant to disseminate audio and video signal, messages, information or programs to wide range of audience. Radio and television are already playing a role in educating the populace non-formally through various educational channels and programs, but there is significant potential to capitalize on their ability to enhance development and learning curriculum content among secondary school students. This study: 1) Find out the awareness of educational radio and television programs by secondary school students in Ogbomoso 2) Investigate secondary school students access to educational radio and television programs in Ogbomoso and 3) Investigate problems militating against students' use of educational radio and television programs for learning. Questionnaire was used as instrument to elicit responses from 100 secondary school students on their awareness-on and access to seven educational radio and television programs. The findings revealed that the students were not aware of the educational radio and television programs even though they have access to it. The study recommends that teachers in secondary schools should include educational broadcasts as forms of stimulus variation that they could apply to their classes and educational programs producers on both radio and television should create enough awareness about the programs to enable students follow the programs at appropriate time.
Keywords: Access to Education; Audiovisual Instruction; Barriers; Distance Education; Educational Radio; Educational Television; Familiarity; Foreign Countries; Questionnaires; Secondary School Students; Student Surveys

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
Keywords: _yl:i; dode_eth-src-dode; dode_eth-trf2-dode

A Study of the Application of Information Technology in Distance Education in Pakistan - Gujjar, Aijaz Ahmed; Ahmed, Saira Ijaz; Ramzan, Muhammad (Journal of Educational Technology, 2011)
Education plays a vital role to develop the nation culturally, economically and socially. That is why every nation focuses on this sector. For its improvement all endeavors are being made through formal education, Non-formal education and Distance Education. The trend of distance education has developed considerably in developed countries and developing countries. Information technology plays a pivotal role for the development of Distance Education. Keeping in view the importance of I.T. in education, this study was developed. The main aim of this study was to investigate the use of information technology in distance education in Pakistan. Population comprised of the I.T. users, person helping, operating or supervising the I.T. tools as planners, academicians, designers, programmers, producers, operators, regional directors and Deans of AIOU. Questionnaire on five point Likert scale was prepared. Collected data was tabulated and analyzed. The main conclusions of the study are: The use of information technology is still limited. Computer net work was not used for distance learners, Radio, T.V. programs and relevant audio material, videocassettes were prepared and CDs, software still not in use. University library was not computerized. Staff got training from time to time in I.T. Education in their specialization. But there is need to make I.T. system more sophisticated according to new trends and students' needs. There is also need to develop regional centers, which should serve as resource centers to the facilitation of distance learners.
Keywords: Access to Information; Data Analysis; Data Collection; Distance Education; Electronic Libraries; Foreign Countries; Information Technology; Likert Scales; Nonformal Education; Open Universities; Questionnaires; Radio; Scores; Statistical Analysis; Student Needs; Technology Uses in Education; Television; Trend Analysis; Use Studies

Final Report of the Somali Interactive Radio Instruction Program - EDC; USAID (2011)

How The Radio Can Reach The World’s Most Vulnerable Children - Lister, Josephine (2019)

Interactive Radio Instruction Brings Learning Back to Eastern Democratic Republic of the Congo - War Child Canada (2017)

Exploiter le potentiel des TIC : Programmes efficaces d'alphabétisation et de numératie utilisant la radio, la télévision, la téléphonie mobile, les tablettes et les ordinateurs - UNESCO (UNESCO Institute for Lifelong Learning, 2017)

Philippines: National Demographic and Health Survey - USAID (2017)

Playing Every Day on Sesame Street - Foulds, Kim; Bucuvalas, Abby (American Journal of Play, 2019)
Keywords: ⛔ No DOI found

Taonga Market Programme Review - USAID (2010)

Final Evaluation Report: Evaluation of Africa Educational Trust’s Speak Up II in South Sudan - Schulze, Charles (African Education Trust, 2019)

Patronage of Educational Broadcasts and its Effects on Academic Growth of Students of Winneba and Apam Senior High Schools in the Central Region of Ghana. - Yelkpieri, Daniel; Kweku, Wilson Esia-Donkoh; Kwesi (Academic Leadership: The Online Journal, 2011)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Patronage of Educational Broadcasts and its Effects on Academic Growth of Students of Winneba and Apam Senior High Schools in the Central Region of Ghana. - Yelkpieri, Daniel; Kweku, Wilson Esia-Donkoh; Kwesi (Academic Leadership: The Online Journal, 2011)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Bangladesh Primary Education Annual Sector Performance Report (ASPR) 2019 - Directorate of Primary Education (2019)

Education Needs Assessment Report - Sierra Leone - Plan International (2016)

The role of Kilimani Sesame in the healthy development of Tanzanian preschool children - Borzekowski, Dina L. G.; Macha, Jacob E. (Journal of Applied Developmental Psychology, 2010)
Kilimani Sesame, a media intervention that employs print, radio, and television, was developed to entertain and educate preschool children in Tanzania. This study examined the effects of a six-week intervention delivering Kilimani Sesame material to 223 children in the rural district of Kisarawe and the city of Dar es Salaam. Results offer evidence that literacy and numeracy, social and emotional development, and health and hygiene significantly improved from baseline to post-intervention; those with the greatest receptivity to Kilimani Sesame performed the best after the intervention, controlling for baseline scores, sex, age, location, and general media receptivity. This study shows that an educational media intervention directed towards very young children can have an impact on their healthy development, even in locales where populations have minimal resources and face extreme hardships.
Keywords: African children; Educational television; Literacy; Media receptivity; Preschool children; Sesame Street

Linguistic imperialism and language decolonisation in Africa through documentation and preservation - Agyekum, Kofi (African linguistics on the prairie, 2018)
This paper addresses the politics of language use in African nations and societies. It highlights the role of power and economics in the choice of language. It discusses linguistic imperialism and language shift, and how they lead to language endangerment. The paper also discusses linguistic decolonization whereby societies resist linguistic domination and endangerment and embark on language maintenance. It touches on the methods employed in language decolonisation, namely language revitalisation, resistance, maintenance, documentation and preservation. Attention will be on lexicology, terminology and the role of radio and TV. We argue that as a society tries to redeem itself from linguistic imperialism through decolonisation, certain stronger politico-economic factors push it back into linguistic imperialism. We will find out that some of the indigenous people themselves kick against language decolonisation. The paper hinges on the theoretical base of language endangerment. Examples are taken from African and Ghanaian languages with emphasis on Akan.

Role of Educational Technology at Primary School Level In District Karak (Khyber Pukhtunkhwa) Pakistan - Suleman, Dr (International Journal of Academic Research in Business and Social Sciences, 2011)
The study was conducted to explore the role of educational technology at primary school level in District Karak (Khyber Pukhtunkhwa). The main objectives of the study were; to investigate the availability, usability and importance of educational technology; and to investigate whether primary school teachers are for the effective use of technologies for teaching learning process. The study was descriptive in nature. All the teachers and students at primary level in District Karak constituted the population of the study. Only three hundred and sixty six (366) primary school teachers; and two thousand and two students (2002) of primary schools (@ of 25% and 5% respectively) were selected randomly as sample of the study. The study was descriptive in nature. Two different questionnaires were prepared for teachers and students for the collection of data. After analysis of data, the researcher arrived at results that educational technology is very useful for the effective teaching learning process at primary level. It was found that educational televisions, radios, film strips, flip charts, VCRs, overhead projectors, multimedia projectors, educational softwares, computers, and internet facilities were not available in schools. Majority of the teachers were not using the available technology in their teaching learning process. It was also found that teachers were not trained for the effective utilization of educational technology.
Keywords: ⛔ No DOI found

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Pre-primary teachers’ preparedness in integrating information and communication technology in teaching and learning in Tanzania - Tandika, Pambas Basil; Ndijuye, Laurent Gabriel (Information and learning science, 2019)
Purpose Integration and use of technology in teaching and learning in the education sector from pre-primary education (PPE) to the higher levels of education, is a policy issue. In developed countries, including Tanzania, information and communication technology (ICT), especially in PPE, is inadequately researched for laying evidence on its applicability in instruction and learning. Therefore, this paper aims to determine pre-primary teachers’ preparedness in integrating ICT in classroom instruction and challenges teachers face in integrating it for child’s meaningful learning. Design/methodology/approach Methods and instruments: a qualitative transcendental phenomenological approach was used in determining teachers’ preparedness in integrating ICT in PPE in Tanzania. It was further used to collect data that describe the teaching and learning through the integration of ICT in every session as their lived experience for pre-primary teachers. Its selection was appropriate as it allowed researchers to systematically analyse for description the commonalities and differences existing among the involved teachers in integrating ICT in teaching and learning as their lived experiences (Moerer-Urdahl and Creswell, 2004). To appropriately analyse teachers’ understanding and experiences regarding ICT and its integration in teaching and learning in pre-primary classes, semi-structured interviews and open-ended questionnaires were used for in-depth understanding of the study problem. Semi-structured interviews were used to collect data through open-ended questions where researchers took an average of 40 min per session with participants’ (teachers) using notebooks to take note of their thoughts, feelings and beliefs about ICT integration in PPE. Use of the semi-structured interview was based on the reality that it provides in-depth information pertaining to participants’ experiences and viewpoints of a particular topic (Turner, 2010). Once the interview session was complete, each teacher was given a questionnaire to fill in for triangulating their experiences. Description of participants: a total of 14 schools constituting 28 teachers were purposively sampled and engaged in this study. Analysis of participants’ demographic characteristics indicates that all of the involved teachers had certificate in teacher education that qualified them as primary school teachers. Meanwhile, 18 (66.7 per cent) of the pre-primary school teachers who were involved in this study were female with only 10 (33.3 per cent) had working experience at and above five years of teaching in early grade classes. Study participants (teachers) from Itilima and Meatu Districts were purposively involved in the study as their experiences in young children’s learning and contextual influences (educational and training policy of 2014, the ICT policy of 2007, and foreign studies) are potential in improving the quality of learning. Study area: the current study was conducted in two districts (Itilima and Meatu) all found in Simiyu region. The two districts were selected and considered appropriate by the study as they constituted the 17 most disadvantaged rural areas in Tanzania (Mosha et al., 2015). Authors describe the two districts as having poor educational outcomes mainly relatively low pass rates in the primary school leaving examination results. In Itilima, one ward out of 22 was studied in which its six schools [with a total of 12 teachers] among 87 schools in the district were involved. While in Meatu district, eight of 121 schools [with a total of 16 teachers] in one ward of 29 wards were studied. This implies that a total of 14 schools and 28 teachers were involved in this study. Data analysis: the data collected through the interviews and open-ended questionnaires were subjected to content analysis procedures (reading and re-reading notes and transcripts followed by a three-steps-coding process consisting of open, axial and selective coding procedures). The analysis process was informed by the Vagle’s (2014) six steps for phenomenological research data analysis procedure (holistic reading of the entire text, first line-by-line reading, follow up questions, second line-by-line reading, third line-by-line reading, and subsequent readings). Practically, the researchers read and re-read the texts and transcribed data from the language used during data collection that is Kiswahili, into the reporting language that is English. Following transcription, data were coded for developing categories of data through axial and elective coding processes. Findings The data analysis was conducted and results and its discussion are presented in three sub-sections: preparedness of teachers in using ICT in teaching and learning; teachers’ views about the integration of ICT in teaching and learning; and challenges faced by teachers in integrating ICT in teaching and learning. Teacher’s preparedness in the use of ICT in teaching: exploration of teachers’ preparedness in integrating ICT in teaching and learning was preceded by exploration of teachers’ understanding of ICT in teaching and learning. Analysis revealed that majority of teachers were aware about ICT in teaching and learning and they understood it as the implementation of curriculum at school level that involves use of ICT-based facilities such as television, mobile phones, computer and radio. Teacher elaborated that appropriate use of ICT-based facilities that would later develop children to potentially improve their understanding and practical application in daily life. Other teachers understood ICT in teaching and learning as use of printed materials [newspapers and magazines] in facilitating pupil’s learning of planned lessons. While other teachers were aware of what ICT means the second category of teachers as noted in their responses, had limited understanding, as to them, ICT in education meant use of printed materials. Difference in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as use of ICT facilities in developing children’s competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Their views are based on the development of children with competencies useful in facilitating further learning in the subject known as Teknolojia ya Habari na Mawasiliano. Following the question based on exploring teachers’ understanding of ICT in teaching and learning, researchers explored teachers’ preparedness in using ICT in teaching and learning. Table 1.0 illustrates teachers’ multiple responses regarding their preparation. Table I: teacher’s preparedness in using ICT in teaching and learning. S/N; preparedness; freq; and per cent. Enhancing child’s understanding on the use of ICT-based facilities-20, 71.4; using remedial sessions teaching ICT-12, 42.8; using ICT-based facilities for teaching other classes-8, 28.5. Table 1.0 illustrates that teachers are prepared to enable children use ICT to access information and more knowledge related to their school subjects and general life. They were of the view that ICT could serve well in areas where text and supplementary books are scares or torn-out by pupils because were poorly bound or due to poor quality of papers used. Therefore, availability of ICT facilities in schools would become important resource-materials for pupils, as well as teachers. For instance, a teacher said that; Availability of ICT facilities, such as computers in schools will help us in preparing notes or content for supplementing their learning. Different from the paper-based notes, computers will keep our notes properly compared to the papers that get easily displaced and hard to retrieve notes when lost (Interview, 20 April 2016). In addition to the use of ICT facilities in serving as resource material, their use in schools would aid pupils and teachers to use them beyond teaching and learning. Teachers narrated that children may find games and puzzles that all help in stimulating their thinking, hence interest in schooling and further learning. Teachers also said they are prepared to use even extra hours that are beyond school timetable to ensure children learn well to meet the uncovered periods once facilities are placed in school. Use of extra hours beyond the normal school timetable comm. Research limitations/implications The study was limited to the accessed and involved schools as some schools were found to have no specific teachers teaching a pre-primary class on reasons the responsible teacher for the class had retired. As a result, researchers spend extended time to travel and reach schools that were located far from one school to the other. Again, some teachers were reluctant in participation on reasons that researchers are evaluating their competency for reporting to the higher authorities. Practical implications Differences in teachers’ understanding of the ICT in teaching and learning also indicate some teachers viewing it as the use of ICT facilities in developing pupils’ competencies in the specific subject. In the teachers’ views, ICT is considered as subject content and they delimited their understanding into that perspective ignoring it as technological use for facilitating meaningful learning in all subjects. Effective integration of ICT for efficiency in instruction depends on the teacher’s preparedness especially competency in using the equipments and infrastructures especially electric power. Social implications Integration of Information and Communication Technology in teaching and learning in PPE is socially important in the view that all children regardless of their background (urban or rural, affluent or poor) benefits in learning through use of technology. The children’s access to education integrating ICT would ensure equal opportunities
Keywords: Information and communication technology; Learning and quality instruction; Pre-primary education; Preparedness; Teaching